PEMIKIRAN HUKUM ISLAM; (Studi Pembaruan Hukum Islam Asy-Syatibi & Ibnu Taimiyah) - Mahdi Abdullah Syihab (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2017)
This article would like to explain about Fiqh thought of Asy Syatibi and Ibnu Taimiyah around Islamic Law. These two figures are known as innovators in Islamic Law. Asy Syatibi is popular in Granada and his thought in Islamic law certainly influenced by social culture in Granada. He applies the principle of “Mura’at al-Khilaf”, which is a principle to honor dissenting opinion in a way that look at all the opinion as correct. Contrary to Ibnu Taimiyyah, his thought in Islamic law influenced by social culture in Damascus. As a result, the basic principle of Ibnu Taimiyyah’s fatwa more resemble to Ahmad ibn Hambal’s thought in the use of existing legal sources. Neverthless, Ibnu Taimiyyah keep looking “illat” (legal reasoning) and base his opinion to that “’illats”.